A qualitative study of dementia caregivers' lived experiences in Singapore - Ang, Chin-Siang (2023)
Globally, the number of people living with dementia is expected to triple by 2050 owing primarily to the aging population. Dementia is a chronic and progressive disease that affects an estimated 5-8% of the general population aged 60 and above at any given time. This qualitative study aimed to investigate caregivers' overall perceptions, challenges, and coping strategies in dementia care in Singapore. Purposive sampling was used to select the study's sample. Eight Singaporeans were interviewed in semi-structured, in-depth interviews. Three themes emerged from the data analysis for each research question: overall perceptions (i.e. less freedom, strained family relationships, and improved self-competency), challenges (i.e. managing dementia symptoms, emotional drain, and decision-making), and coping mechanisms (i.e. making time for myself, religious belief, and seeking external support). Knowing about these challenges and coping mechanisms allows practitioners to help caregivers to reduce personal struggles, thus improving the patient's and caregiver's quality of life.